Clinical comparative study of conventional cesarean section versus Pelosi's technique - Cienfuegos Solís, Héctor (2015)
OBJETIVE: To compare the features and morbidity associated with the conventional technique of cesarean and cesarean Pelosi technique. DESIGN: Retrospective, comparative, descriptive study. LOCATION: Department of Obstetrics Hospital I "Uldaric Rocca Fernández" (EsSalud). MATERIALS AND METHODS: 162 medical records of patients who underwent cesarean section between 2001 and 2002 were reviewed; 81 of which were conducted with the conventional technique and other 81 with Pelosi technique. Operating time, presence and type of complications, blood loss, restart time oral intake and postoperative hospital stay, using a special statistical profile was determined. RESULTS: The main indications in both groups were acute fetal distress (SFA) and a history of previous cesarean. The operative time was 34.8 minutes in the technique vs. Pelosi 51.7 minutes in the conventional art. As for the time of resumption of oral intake, technical Pelosi was 8.2 hours vs. 14.2 hours in the conventional art. Hemoglobin decreased to 1.21 g% vs. technical Pelosi 2.22 g% with the conventional technique. The main complication in both groups was wound infection (6.2% vs. 4.9% conventional in Pelosi). CONCLUSIONS: Cesarean section rate Pelosi technique is a safe alternative choice of operative delivery, including previous cesarean. It is suggested that similar studies in other hospitals of the Minsa and EsSalud, to verify the advantages of this surgical technique.